2018
DOI: 10.1371/journal.pone.0194530
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression in serum samples of sulfur mustard veterans as a diagnostic gateway to improve care

Abstract: Sulfur mustard is a vesicant chemical warfare agent, which has been used during Iraq-Iran-war. Many veterans and civilians still suffer from long-term complications of sulfur mustard exposure, especially in their lung. Although the lung lesions of these patients are similar to Chronic Obstructive Pulmonary Disease (COPD), there are some differences due to different etiology and clinical care. Less is known on the molecular mechanism of sulfur mustard patients and specific treatment options. microRNAs are maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In haematology, miR-191-5p is overexpressed in poor prognostic acute myeloid leukaemia 47 . miR-16 is the most frequently used as RG in several models and in circulating miRNA analysis [48][49][50][51][52][53][54][55] but always with another miR. miR-16 is the most frequently used as RG in several models and in circulating miRNA analyses, always combined with another miR.…”
Section: Discussionmentioning
confidence: 99%
“…In haematology, miR-191-5p is overexpressed in poor prognostic acute myeloid leukaemia 47 . miR-16 is the most frequently used as RG in several models and in circulating miRNA analysis [48][49][50][51][52][53][54][55] but always with another miR. miR-16 is the most frequently used as RG in several models and in circulating miRNA analyses, always combined with another miR.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have determined the role of miRNAs in the development of various diseases (7,(30)(31)(32) and further research has revealed that miRNAs are involved in the development of various types of cancer (33-36). Many studies have also identified the aberrant expression of certain miRNAs in tumor cells and thus are considered novel references for tumor diagnosis (37,38). miRNAs are novel therapeutic targets and may serve as prognostic indicators (34).…”
Section: Discussionmentioning
confidence: 99%
“…Sulfur mustard (SM; bis(2‐chloroethyl) sulfide), a potent vesicant 1 used against humans, continues to be recognized as a threat agent 2,3 . Stockpiles of SM and similar chemicals still exist, and the threat of intentional or accidental exposures is ever increasing 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that nucleic acids, including microRNAs (miRNAs), can influence the inflammation and coagulation pathways as well as other pathways involved in tissue injury and repair. Recent data have indicated the presence of altered expression of miRNAs in SM‐exposed individuals, 1 and a possible role of miRNAs in determining sensitivity to SM 17 . However, beyond preliminary reports on the differential expression of individual miRNAs in SM‐induced injury, not much is known.…”
Section: Introductionmentioning
confidence: 99%